PRESUPPOSITION ANALYSIS IN SOME SELECTED CONSUMER ADVERTISEMENT SLOGANS OF THE JAKARTA POST - Sinta Ananda; Marwito Wihadi; Yayan Suryana (English Review: Journal of English Education, 2016)
This research investigates the presupposition in the slogans of consumer advertisement of the Jakarta Post newspaper on March 2016 edition. This research aimed at finding the types of presupposition and describing the functions of presupposition in advertisement found in consumer advertisement slogans of the Jakarta post newspaper. Yule’s theory and descriptive qualitative research method applied in this research. 20 slogans of consumer advertisement of the Jakarta Post newspaper on March 2016 edition selected to this research. The result of this research showed that the writer found 20 presuppositions. 11 existential presupposition or 55%, 4 factive presupposition or 20%, 3 lexical presupposition or 15%, and 2 non-factual presupposition or 10%. Regarding the function of presupposition in advertisement, the writer found 17 slogans advertisement contains implicit competition, and 11 slogans advertisement contains making the advertisement short and memorable. In conclusion, not all type of presupposition and function of presupposition in advertisement are found, it is influenced by various types and functions in advertisement causing different assumption and presupposition. The writer hopes that further researchers who are interested in observing presupposition to explore more about presupposition in other types of advertisement.Keywords: presupposition, consumer, advertisement, slogan